Effects of periodical drying and non-drying on nutrient content and desiccation tolerance of an intertidal Pyropia yezoensis strain subject to farming conditions - Wang, Wen Jun; Li, Xiao Lei; Sun, Teng Qing; Liang, Zhou Rui; Liu, Fu Li; Sun, Xiu Tao; Wang, Fei Jiu (Journal of applied phycology, 2019)
Aquaculture of Pyropia yezoensis is extending from shallow seawater to deep seawater in China where full-floating culture protocol is applicable. The current P. yezoensis cultivars come from intertidal parents and have been long subject to periodical drying (PD) culture protocols. To investigate whether these cultivars acclimate to a full-floating non-drying (ND) culture protocol, an intertidal P. yezoensis cultivar was cultured with ND and PD protocols. It was found that protocols with and without PD affected dehydration tolerance and nutrient components differently during farming. The maximum quantum yield of PSII ( F v / F m ) of the thalli from both systems decreased during dehydration. During rehydration, F v / F m of the thalli from the PD system fully recovered after 70% relative water loss (RWL), whereas F v / F m of the thalli from the ND system failed to fully recover from 50% RWL. During dehydration, superoxide dismutase, peroxidase, and catalase activities in the thalli cultured with ND were much lower than those in the thalli from PD systems. Nevertheless, the activity of superoxide dismutase + peroxidase + catalase was similar in the fresh thalli from both systems. Compared to the PD system, the thalli from the ND system contained lower levels of soluble proteins, chlorophyll a , carotenoids, total fatty acids (FA), and C16:0 FA but higher levels of total amino acids (AA), delicious AA, unsaturated FA, and eicosapentaenoic acid. Contents of phycocyanin, allophycocyanin, and essential AA were similar in both systems. In summary, there were pros and cons of using either system for P. yezoensis cultivation. Diversified Pyropia culture protocols should be applied depending on seawater depth and requirements of varying nutrient components.